2020
DOI: 10.1037/dev0001089
|View full text |Cite
|
Sign up to set email alerts
|

Joint attention partially mediates the longitudinal relation between attuned caregiving and executive functions for low-income children.

Abstract: Using data from a large longitudinal sample (N = 1,292) of children and their caregivers in predominantly low-income, nonurban communities, we investigated longitudinal relations between attuned caregiving in infancy, joint attention in toddlerhood, and executive functions in early childhood. The results from path analysis demonstrated that attuned caregiving during infancy predicted more joint attention in toddlerhood, which was in turn associated with better executive function performance in early childhood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Their early diagnostic value notwithstanding, the early emergence of social attention symptoms also likely reflects primary if not congenital neurodevelopmental mechanisms of the complex endophenotype of ASD (9,16,(39)(40)(41)(42). Moreover, early social attention symptoms are thought to be associated with significant differences in early socialinformation processing that contribute to the developmental perturbations in learning, social communication, and cognition that are characteristic of older autistic children (16,39,(43)(44)(45). This "developmental cascade hypothesis" of social attention symptoms has motivated researchers to develop methods to target interventions for joint attention, social orienting, and eye contact in young children (46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Their early diagnostic value notwithstanding, the early emergence of social attention symptoms also likely reflects primary if not congenital neurodevelopmental mechanisms of the complex endophenotype of ASD (9,16,(39)(40)(41)(42). Moreover, early social attention symptoms are thought to be associated with significant differences in early socialinformation processing that contribute to the developmental perturbations in learning, social communication, and cognition that are characteristic of older autistic children (16,39,(43)(44)(45). This "developmental cascade hypothesis" of social attention symptoms has motivated researchers to develop methods to target interventions for joint attention, social orienting, and eye contact in young children (46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not see differences between individuals with UBN and SBN in the Anot-B and Spatial Reversal task, our sample overall identified as low to mid-SES and it is possible, we could see more differentiation with more variability in SES. Also, the lack of differences could be due to the task impurity problem in this age range and lack of measures of parenting abilities, caregivers-infant interactions, and informal activities (e.g., playing ball games, clapping, and drawing) in the different SES groups, which could serve as a protective factor of poverty (Bernier et al, 2011;Brandes-Aitken et al, 2020). Having said that, we did see that child with UBN showed shorter latencies on the snack delay compared to children with SBN.…”
Section: Discussionmentioning
confidence: 99%
“…In young preschoolers and toddlers, these communications skills are often developing so relations to language and communication more broadly defined (e.g., joint or shared attention, gesture) have been examined. For example, within the second year a number of studies have linked EF-related abilities to non-verbal communication related to gestures, with authors suggesting: (a) private gestures have the function of directing infants' behavior (Basilio & Rodríguez, 2017;Kuvalja et al, 2013), (b) cognitive abilities common to EF link to gestures and language (Kuhn et al, 2014(Kuhn et al, , 2016, and (c) during joint attention episodes parents scaffold basic components of cognitive control (Brandes-Aitken et al, 2020). In addition, studies have found EF links to initiating joint attention (i.e., IJA, internally motivated sharing of interest and experiences with adults), with authors suggesting infants must represent and reflect on the representation to guide sharing behavior (Miller & Marcovitch, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brandes-Aitken et al ( 2020 ) demonstrated the importance of the primary caregiver in an analysis using data from the Family Life Project (FLP; described in a later section). The authors examined relations among attuned caregiving (i.e., the caregiver's sensitive behavior including appropriate contingency and matching based on the child's developmental and emotional needs) at 15 months, joint attention at 24 months, and executive function at 48 months.…”
Section: The Caregiver Is the Key In Promoting Hierarchical Integrati...mentioning
confidence: 99%